Tio2 Doped with Noble Metals as an Efficient Solution for the Photodegradation of Hazardous Organic Water Pollutants at Ambient Conditions - Soto-Donoso, N; Soto-Donoso, N (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
This work highlights new insights into the performance of TiO2 doped with noble metal catalysts for the photocatalytic degradation of organic water pollutants. Different samples of titanium dioxide doped with noble metals (Au and Pd) were successfully synthesized via incipient wet impregnation (IWI) and ultrasound-assisted impregnation (US) methods. X-ray diffraction, scanning electron microscopy and UV-Vis reflectance spectroscopy were used for the characterization of the obtained materials. Their photocatalytic efficiency was investigated in aqueous suspension thorough a series of laboratory tests performed under ultraviolet (UV-A) irradiation conditions using 2,4 dinitrophenol (2,4 DNP) as a target molecule. The results clearly show that the method used for the catalyst synthesis affects its photocatalytic activity. It was found that the samples prepared by the IWI method exhibited high photocatalytic activity, and the removal rate obtained with TiO2-Pd/IWI was higher than that found for TiO2-Au/IWI. Furthermore, for the best catalyst, some extra photocatalytic experiments were conducted with rhodamine 6G (R6G), a highly stable molecule with a very different chemical structure to 2,4 DNP, in order to check the reactivity of this material. Moreover, the recycling experiments carried out with TiO2-Pd/IWI clearly demonstrated the high photocatalytic stability of this material for the degradation of 2,4 DNP. All of the collected data confirmed the interesting photocatalytic potential of the selected catalyst in the elimination of organic pollutants with no obvious change in its reactivity after four reaction cycles, which is very promising for promoting future applications in water depollution. © 2020 by the authors. Licensee MDPI, Basel, Switzerland